Cost comparison of asthma treatments in 12-week study: caution about matching and short observational follow-up. Issue 1 (December 2016) - Price, David; van Boven, Job; Law, Lisa; Cifra, Alessandra; McQueen, R.
Abstract In the absence of randomisation, observational studies must take extra care to create treatment groups that are comparable in terms of key characteristics. Various matching methods exist which can create sound comparisons, minimising confounding where possible. A recent observational study by Dal Negro et al. carried out a cost analysis comparing two asthma medications. They report strong conclusions which favour one treatment over the other, however they include little discussion on the limitations of their study. The purpose of this letter is to comment on the weaknesses of the study design, including the level of matching used, and to urge readers to consider these issues alongside the interpretation of results.